2021
DOI: 10.1152/japplphysiol.00147.2021
|View full text |Cite
|
Sign up to set email alerts
|

Case Studies in Physiology: Temporal variations of the lung parenchyma and vasculature in asymptomatic COVID-19 pneumonia: a multispectral CT assessment

Abstract: This study reports systematic longitudinal pathophysiology of lung parenchymal and vascular effects of asymptomatic COVID-19 pneumonia in a young, healthy never-smoking male. Inspiratory and Expiratory non-contrast along with contrast Dual-energy computed tomography (DECT) scans of the chest were performed at baseline on the day of acute COVID-19 diagnosis (Day 0), and across a 90 day period. Despite normal vital signs and pulmonary function tests on the day of diagnosis, the CT scans and corresponding quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…C1 was characterized by increased lung tissue during inspiration, greater amount of GGO patterns, and thickening bronchovascular structure, which are known phenotypes associated with the inflammation caused by the infection of COVID-19. Another study has suggested that even in mild cases, return of increased GGO can still be observed after 90 days from the diagnosis of COVID-19 ( Nagpal et al, 2021 ). Furthermore, increased air-trapping due to small airways disease (AirT_fSAD% ↑, Tissue_RV % ↓ ) was found in C1 subjects.…”
Section: Discussionmentioning
confidence: 99%
“…C1 was characterized by increased lung tissue during inspiration, greater amount of GGO patterns, and thickening bronchovascular structure, which are known phenotypes associated with the inflammation caused by the infection of COVID-19. Another study has suggested that even in mild cases, return of increased GGO can still be observed after 90 days from the diagnosis of COVID-19 ( Nagpal et al, 2021 ). Furthermore, increased air-trapping due to small airways disease (AirT_fSAD% ↑, Tissue_RV % ↓ ) was found in C1 subjects.…”
Section: Discussionmentioning
confidence: 99%